2016
DOI: 10.18632/aging.101056
|View full text |Cite
|
Sign up to set email alerts
|

Global gene profiling of aging lungs in Atp8b1 mutant mice

Abstract: ObjectiveRecent studies implicate cardiolipin oxidation in several age-related diseases. Atp8b1 encoding Type 4 P-type ATPases is a cardiolipin transporter. Mutation in Atp8b1 gene or inflammation of the lungs impairs the capacity of Atp8b1 to clear cardiolipin from lung fluid. However, the link between Atp8b1 mutation and age-related gene alteration is unknown. Therefore, we investigated how Atp8b1 mutation alters age-related genes.MethodsWe performed Affymetrix gene profiling of lungs isolated from young (7-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“…We therefore investigated whether either feature was associated with increased ACE2 expression. In four different cohorts of aging mice and one cohort of aging rats, we did not detect a significant age-dependent change in ACE2 expression in the lung (Figures 1A, 1B, and S1D-S1F) (The Tabula Muris Consortium et al, Jonker et al, 2013;Misra et al, 2007;Soundararajan et al, 2016;Yu et al, 2014). Similarly, ACE2 expression in rodent lungs was not significantly different between sexes (Figures 1C and 1D) (Crowley et al, 2015;Yu et al, 2014).…”
Section: Ace2 Levels In Mammalian Lungs Are Not Strongly Affected By Age or Sexmentioning
confidence: 74%
“…We therefore investigated whether either feature was associated with increased ACE2 expression. In four different cohorts of aging mice and one cohort of aging rats, we did not detect a significant age-dependent change in ACE2 expression in the lung (Figures 1A, 1B, and S1D-S1F) (The Tabula Muris Consortium et al, Jonker et al, 2013;Misra et al, 2007;Soundararajan et al, 2016;Yu et al, 2014). Similarly, ACE2 expression in rodent lungs was not significantly different between sexes (Figures 1C and 1D) (Crowley et al, 2015;Yu et al, 2014).…”
Section: Ace2 Levels In Mammalian Lungs Are Not Strongly Affected By Age or Sexmentioning
confidence: 74%
“…Loss of Nrf2 expression can be a consequence of aging [9, 10], functional polymorphisms [11], and/or fibrotic TGF-β/pSmad3 signaling [1215]. Preclinical models of pulmonary fibrosis indicate that Nrf2 is suppressed as the disease progresses [16, 17] and that haploinsufficiency is sufficient for enhanced susceptibility [8].…”
Section: Introductionmentioning
confidence: 99%
“…Increased airway cardiolipin secretion and development of pneumonia were detected in type 2 cells of mice with a functional mutation (G308V) in a cardiolipin transporter (ATPase, aminophospholipid transporter, class I, type 8B, member 1, ATP8B1) (Ray et al 2010). In addition, decreased lung NRF2-ARE responses were found in the aged Atp8b1 mutant mice (14 month) compared to aged wildtype mice (Soundararajan et al 2016). Overall, these studies indicated that cardiolipin homeostasis may be protective in age-related lung disorders.…”
Section: Pneumonia Acute Lung Injury and Other Airway Disordersmentioning
confidence: 70%